Upaya Mengenalkan Produk UMKM Damar Kurung Melalui Studi Independen Sekolah Ekspor - Jovansa N. K. Dheva; Moch. T. Safirin (Journal of Student Research, 2024)
Damar Kurung is a typical Gresik city art product and has considerable market and export potential. With the Export School Independent Study program "Be a Digital Exporter", it is expected to be able to introduce Damar Kurung products to local and international markets. Efforts need to be made to be able to utilize the potential that exists in regional MSME products, one of which is the Independent Study of the Export School "Be a Digital Exporter" held by Merdeka Campus. The research method used a qualitative approach with a descriptive method. Data collection is carried out using observation and documentation techniques from the results of observations that can be concluded. The results of this study are Through the Sang Damar company created in groups in the Independent Study program of the Export School, we introduce and try to market Damar Kurung products. It is hoped that in this way it can boost the development of regional MSMEs in Indonesia, especially in Damar Kurung products typical of the city of Gresik.